Effects of Climate Change on Sudan's Water Resources - Hanaa Tharwat, Mohamed Ibrahim; Modiba, Maimela Maxwell; Simon, Barbara (Journal of Central European Green Innovation, 2023)
In Sudan, the effects of climate change on water resources are widespread and varied. Sudan's water sources are diverse, including river, rain, surface, and groundwater, with the country's lands consisting of rivers, valleys, and creeks. Nevertheless, Sudan faces various water-related challenges such as inadequate sanitation, lack of safe drinking water, pollution, and scarcity. The country's water supply is at risk due to rapid population growth, urbanization, changing consumption patterns, and from agriculture, industry, and energy sectors. Moreover, the looming environmental changes, including global warming and increased greenhouse gas emissions, are expected to have significant social, environmental, and climatic impacts globally, particularly on water sources. The effects of climate change on Sudan's water resources are a cause for concern as droughts have already begun in some regions. It is therefore imperative to reduce greenhouse gas emissions and adopt clean energy sources while taking urgent and long-term measures to conserve water and mitigate climate change risks. This review highlights the issues related to climate change and its effects on water resources in Sudan, with a particular focus on how changing rainfall patterns will impact agriculture, which is the most critical indirect effect of climate change on water supply.